A Literature Review: Antimicrobial Phenolic Compounds in Nutmeg (Myristica fragrans Houtt) - Ipaenin, Jahiria; Chabib, Lutfi; Hasnaeni, Hasnaeni; Tunny, Risman (Universitas Pendidikan Mandalika, 2025)
In various countries, testing of phenolic compounds in plants is always carried out because these compounds have various health benefits such as antioxidant, anti-inflammatory, and antimicrobial activities. The types of medicinal plants in Indonesia are known to be very diverse where those included in the medicinal plant group reach more than 1000 species, one of which is nutmeg (Myristica fragrans Houtt.) Nutmeg (Myristica fragrans Houtt.) itself is native to the Maluku Islands, Indonesia. However, besides the Moluccas, nutmeg is also cultivated in several other tropical countries. The main objective of this literature review is to critically examine the antimicrobial properties and identify the specific antimicrobial components of phenolic compounds contained in nutmeg (Myristica fragrans Houtt.) The methodology used in this study involved a comprehensive literature review by utilizing reputable academic databases such as Google Scholar, PubMed, and Science Direct related to articles published between 2019 and 2024. The results of this study were obtained through a thorough search process, resulting in eight articles that were considered to meet the established inclusion criteria. A number of articles showed the effectiveness of nutmeg as an antimicrobial because nutmeg contains phenolic compounds that have antibacterial and antifungal properties, which make it effective as an antimicrobial agent. Therefore, with a more comprehensive understanding of the content of phenolic compounds and their mechanism of action, nutmeg can be a further basis for study in the health sector and the pharmaceutical industry.